2011
DOI: 10.1007/978-3-642-20161-5_87
|View full text |Cite
|
Sign up to set email alerts
|

Towards Predicting Relevance Using a Quantum-Like Framework

Abstract: In this paper, the user's relevance state is modeled using quantum-like probability and the interference term is proposed so as to model the evolution of the state and the user's uncertainty about the assessment. The theoretical framework has been formulated and the results of an experimental user study based on a TREC test collection have been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Following van Rijsbergen's pioneering work, a body of quantum or quantum-like frameworks have recently been developed to formalize retrieval models and have achieved significant improvements [17][18][19][20]. Piwowarski et al [21] attempted to find an effective quantum representation of documents and queries for measuring the relevance between them.…”
Section: Introductionmentioning
confidence: 99%
“…Following van Rijsbergen's pioneering work, a body of quantum or quantum-like frameworks have recently been developed to formalize retrieval models and have achieved significant improvements [17][18][19][20]. Piwowarski et al [21] attempted to find an effective quantum representation of documents and queries for measuring the relevance between them.…”
Section: Introductionmentioning
confidence: 99%
“…Note that similar interpretations of quantum interference within IR have been implicitly suggested by Wang et al [2010], Di Buccio et al [2011] and Melucci [2010]. In the first work, in fact, Wang et al suggested that topics may interfere, thus affecting the relevance assessments of documents.…”
Section: What Does Quantum Interference Mean In Qprp and In Ir?mentioning
confidence: 55%
“…Di Buccio et al [2011] instead studied the interactions between users and documents when assessing the relevance of documents to selected TREC topics. They focused on determining the level of uncertainty in the relevance assessments, claiming that the quantum probability framework, and in particular the notion of quantum interference can correctly update the predicted probability of relevance depending on the evolution of the user's relevance state and the user's uncertainty about the assessment.…”
Section: Motivations For Using Quantum Theory In Irmentioning
confidence: 99%
“…However, it remains unclear as to how we should regard the application of quantum ideas in the information sciences, and how their “quantumness” is regarded. To give just a few examples, it has been described as: A metaphor (Bruza, Kitto, Nelson, & McEvoy, ; Wittek & Darányi, 2011a, 2011b) An analogy (Arafat, ; Piwowarski et al., 2010b; Widdows, ; Zhao et al., ) Inspired by quantum theory (Piwowarski et al., , ; Zhao et al., ) Quantum‐like (Di Buccio et al., ; Haven & Khrennikov, ) An abstract framework (Bruza et al., ) A scientific mirror (Arafat, ) …”
Section: Discussionmentioning
confidence: 99%
“…As a second, we can mention a model that uses the concept of interference to model the way in which relevance judgments of any document are affected by similar judgments of other documents (Zuccon & Azzopardi, ); another analysis of interference is given by Melucci (). A third example is the modeling of users' relevance states by quantum probability (Di Buccio, Melucci, & Song, ). A relevance state is an individual's internal subjective assessment of relevance, which only appears as an objective relevance assessment when a final judgment has been reached: a process analogous to the “collapse” of a physical quantum superposition.…”
Section: Literature Analysismentioning
confidence: 99%